AIEE active novel red-emitting D-π-A phenothiazine chalcones displaying large Stokes shift, solvatochromism and "turn-on" reversible mechanofluorochromism. (October 2020) - Sachdeva, Tanisha; Milton, Marilyn Daisy
Abstract: In an effort to develop red light emitting, AIEE active potential mechanofluorochromic smart materials, a series of novel D-π-A based phenothiazine chalcone derivatives was designed and synthesized. Various aryl groups were appended to the phenothiazine ring with the aim of tuning the donor ability and to regulate the molecular arrangements which could alter the photophysical and mechanofluorochromic (MFC) properties. Photophysical studies revealed an enhanced intramolecular donor-acceptor charge transfer by appending electron donating 4 -methoxyphenyl ring on the phenothiazine moiety whereas a bulky 1 -naphthyl ring led to reduced intramolecular charge transfer character. Experimental band gap energies of all the derivatives were found to be in range 2.58–2.68 eV. Existence of large Stokes shift (143–221 nm) and positive solvatochromism was observed in solvents of differing polarity. All the derivatives exhibited a yellow emission in non-polar solvent (toluene) and red emission in polar solvent (DMSO). Chalcone with naphthyl ring displayed maximum AIEE characteristics. Reversible " off-on-off " mechanofluorochromic behaviour was observed upon the subsequent exposure of mechanical stress and dichloromethane vapours or heat. Single crystal X-ray diffraction pattern analysis indicated the presence of twisted conformations and weak intermolecular interactions which are responsible for the mechanofluorochromic behaviour. Powder X-ray diffraction patterns revealed the transformation from crystalline to amorphous state upon mechanical grinding which were reversed upon exposure of dichloromethane vapours or heat. Graphical abstract: Image 1 Highlights: Design and synthesis of D-π-A based red emissive phenothiazine chalcone derivatives. Tuning of donor ability of phenothiazine by appending different substituents. Positive solvatochromism with large Stokes shift (143–221 nm). Existence of twisted intramolecular charge transfer (TICT) along with aggregation-induced emission enhancement (AIEE). Reversible " turn-on " mechanofluorochromism.